2006
DOI: 10.1021/cm060090s
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Studies on Synthetic and Natural Crystalline Arsenic(III) Sulfide, As2S3 (Orpiment):  New Data for an Old Compound

Abstract: Synthetic monoclinic orpiment was recrystallized by annealing the glass at 523 K for 1 year. The apparent heat of fusion of orpiment at T fus = 601 K (onset) was found to depend linearly on the ratio V/m (V = inner volume of the sample pan, m = in-pan sample mass) because of partial sublimation. This gives Δfus H = 131 J g-1 if V/m = 0 and the specific volume of the vapor phase v(v) = 190 cm3 g-1 if Δfus H = 0 at the conditions of the orpiment−liquid−vapor triple point. Lattice parameters of orpiment and liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…24 although it has been questioned in Ref. 4. We present the kinetic lines of the direct and reverse transitions.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…24 although it has been questioned in Ref. 4. We present the kinetic lines of the direct and reverse transitions.…”
mentioning
confidence: 88%
“…1,2 The As 2 S 3 melt is one of the most important archetypical strong glassforming liquids, whose viscosity of 8000 Pa s near the melting temperature at normal pressure is record high for chalcogenide melts, 3 making the crystallization of As 2 S 3 almost impossible. 4 The As 2 S 3 substance ranks first among chalcogeniges from the viewpoint of the production of amorphous and glasslike industrial materials. The crystalline phase of As 2 S 3 is a semiconductor ͑orpiment͒ with a layer structure, each As atom is surrounded by three S atoms and each S atom by two As atoms.…”
mentioning
confidence: 99%
“…Besson et al, 1980;Devaud et al, 1989). Espeau et al (2006) who could find no evidence for a high-temperature polymorph of As 2 S 3 and summarized their study with the statement ''Thus the existence of another enantiotropically related As 2 S 3 polymorph remains elusive.' ' Besson et al (1980) in their study of the effects of pressure on crystalline As 2 S 3 to 10 GPa were motivated specifically to find a solid-state transition, but concluded that it did not exist.…”
Section: Anorpiment the Triclinic Dimorph Of Orpimentmentioning
confidence: 99%
“…The discovery of a new polymorph of As 2 S 3 is remarkable given the large amount of work that has been done on the synthesis and phase relationships of arsenic sulphides due to interest in their optical and electronic properties (Srivastava et al, 2011) and especially at hightemperatures, because As 2 S 3 is an excellent glass former (Espeau et al, 2006). The known natural phases of arsenic sulphide include the molecular crystals dimorphite, As 4 S 3 ; pararealgar, As 4 S 4 ; realgar, As 4 S 4 ; alacránite, As 8 S 9 ; and uzonite, As 4 S 5 ; and the layer structure orpiment, As 2 S 3 (Gibbs et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory information in literature about a reversible transformation of orpiment into another form (b) recently induced Espeau et al (2006) to study both natural and synthetic orpiment by means of high-temperature powder X-ray diffraction, liquid density measurements and differential scanning calorimetry. According to these authors, the existence of another As 2 S 3 polymorph remains elusive.…”
Section: Layered Structuresmentioning
confidence: 99%